ผลของความหนาแน่นของกระแสไฟฟ้าภายนอกที่มีต่อการส่งผ่านสปิน ในโครงสร้างวัสดุแม่เหล็กสองชั้นที่คิดผลของรอยต่อ The Effect of Current Density for Spin Transport in Magnetic Bilayer with Diffuse Interface - จุรีมาศ, พรรณวดี; บุตรรัตนะ, ชนิตา; จุรีมาศ, เจษฎา (Science Essence Journal, 2016)
บทคัดย่อ พฤติกรรมการส่งผ่านสปินซึ่งแสดงถึงความต้านทานแม่เหล็กปริมาณมากมีค่าขึ้นอยู่กับความหนาแน่นของกระแสไฟฟ้าภายนอกและรอยต่อแบบแพร่กระจายที่เกิดจากการผสมกันของไอออนระหว่างวัสดุที่อยู่ติดกัน งานวิจัยนี้ได้เสนอวิธีการศึกษาการส่งผ่านสปินโดยศึกษาผลของความหนาแน่นของกระแสไฟฟ้าและผลของรอยต่อด้วยรูปแบบจำลองทั่วไปของการสะสมสปินร่วมกับแบบจำลองบริเวณรอยต่อซึ่งสามารถจำลองได้โดยอาศัยกฎของฟิกค์ ความเข้มข้นของไอออนต่อตำแหน่งภายในโครงสร้างวัสดุแม่เหล็กถูกนำไปใช้ในการพิจารณาพารามิเตอร์การส่งผ่านสปิน ซึ่งสามารถนำไปคำนวณการสะสมสปินและความต้านทานแม่เหล็กได้โดยความต้านทานแม่เหล็กคำนวณมาจากการเปลี่ยนแปลงของการสะสมสปิน ในงานวิจัยนี้ได้ศึกษาการส่งผ่านสปินในโครงสร้างวัสดุแม่เหล็กสองชั้นซึ่งประกอบด้วยโคบอลต์กับทองแดงโดยพิจารณาผลของความหนาแน่นของกระแสไฟฟ้าภายนอกและความกว้างของบริเวณรอยต่อ จากผลการศึกษาพบว่าความหนาแน่นของกระแสไฟฟ้าภายนอกเป็นปัจจัยสำคัญที่ส่งผลต่อพฤติกรรมการส่งผ่านสปิน อัตราส่วนของความต้านทานแม่เหล็กมีแนวโน้มที่จะมีค่าเพิ่มขึ้นเมื่อเพิ่มความหนาแน่นของกระแสไฟฟ้าภายนอก นอกจากนั้นความกว้างของบริเวณรอยต่อยังส่งผลต่ออัตราส่วนของความต้านทานแม่เหล็กโดยเมื่อความกว้างของบริเวณรอยต่อมีค่าลดลงความต้านทานแม่เหล็กปริมาณมากจะมีค่าเพิ่มขึ้นเนื่องจากเกิดการกระเจิงของการสะสมสปินที่บริเวณรอยต่อแบบเรียบ Abstract The spin transport behaviour representing giant magnetoresistance (GMR) is influenced by the injected current density and the diffuse interface between layers. The diffuse interface arising from the intermixing of ions of the adjacent materials becomes significant factor on spin transport. In this work, we propose the theoretical approach to investigate the effect of the electrical current density and diffuse interface via the generalised spin accumulation model coupled with the interface model. The spin accumulation model can be used to describe the spin transport for noncollinear configuration. Meanwhile, the diffuse interface is modeled following Fick's law. The spatial concentration of magnetic ion is used to consider the spin transport parameters which are required for spin accumulation calculation and magnetoresistance. The magnetoresistance is calculated from the gradient of spin accumulation. The bilayer system of Co/Cu is considered here. The effect of electric current density and the width of interface region are studied. We found that the current density significantly affects to the spin transport behaviour. The MR ratio increases with increasing the electrical current density. In addition, the thickness of interface also influences to the MR ratio. MR ratio is likely to increase with decreasing interface thickness. This is due to scattering of spin accumulation of atomically sharp interface.